Antibiotic treatment schemes for very severe community-acquired pneumonia in children: a randomized clinical study - Ribeiro, Cristiane Franco [UNESP]; Ferrari, Giesela Fleischer [UNESP]; Fioretto, José Roberto [UNESP] (Pan Amer Health Organization, 2011)
Objective. To compare clinical response to initial empiric treatment with oxacillin plus ceftriaxone and amoxicillin plus clavulanic acid in hospitalized children diagnosed with very severe community-acquired pneumonia (CAP).Methods. A prospective randomized clinical study was conducted among children 2 months to 5 years old with a diagnosis of very severe CAP in the pediatric ward of São Paulo State University Hospital in Botucatu, São Paulo, Brazil, from April 2007 to May 2008. Patients were randomly divided into two groups by type of treatment: an oxacillin/ceftriaxone group (OCG, n = 48) and an amoxicillin/clavulanic acid group (ACG, n = 56). Analyzed outcomes were: time to clinical improvement (fever and tachypnea), time on oxygen therapy, length of stay in hospital, need to widen antimicrobial spectrum, and complications (including pleural effusion).Results. The two groups did not differ statistically for age, sex, symptom duration before admission, or previous antibiotic treatment. Time to improve tachypnea was less among ACG patients than OCG patients (4.8 +/- 2.2 versus 5.8 +/- 2.4 days respectively; P = 0.028), as was length of hospital stay (11.0 +/- 6.2 versus 14.4 +/- 4.5 days respectively; P = 0.002). There were no statistically significant differences between the two groups for fever improvement time, time on oxygen therapy, need to widen antimicrobial spectrum, or frequency of pleural effusion.Conclusions. Both treatment plans are effective in treating very severe CAP in 2-monthto 5-year-old hospitalized children. The only analyzed outcome that favored amoxicillin/clavulanic acid treatment was time required to improve tachypnea.
Keywords: Pneumonia; anti-bacterial agents; randomized clinical trial; child, preschool; infant; ceftriaxone; oxacillin; amoxicillin; clavulanic acid; Brazil